2020
DOI: 10.1186/s12936-020-03264-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of kelch13 non-synonymous mutations in Plasmodium falciparum isolates from Central African Republic (2017–2019)

Abstract: Background: Over the last decade, artemisinin-based combination therapy (ACT) has contributed substantially to the decrease in malaria-related morbidity and mortality. The emergence of Plasmodium falciparum parasites resistant to artemisinin derivatives in Southeast Asia and the risk of their spread or of local emergence in sub-Saharan Africa are a major threat to public health. This study thus set out to estimate the proportion of P. falciparum isolates, with Pfkelch13 gene mutations associated with artemisin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Our study is in agreement with previous studies conducted in Uganda, 32 , 33 which also recorded new mutations not previously reported in Southeast Asia. A more recent study 34 conducted in Central Africa Republic, a country having close proximity to Uganda, has also reported a non‑synonymous mutation at locus Y653N with a prevalence of 0.5%, a mutation that has not been associated before with artemisinin resistance in Southeast Asia. In addition, other new non-synonymous mutations (M472I; Y558C; K563R; P570L; P615S) have been reported in other places but have not shown any role in conferring resistance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study is in agreement with previous studies conducted in Uganda, 32 , 33 which also recorded new mutations not previously reported in Southeast Asia. A more recent study 34 conducted in Central Africa Republic, a country having close proximity to Uganda, has also reported a non‑synonymous mutation at locus Y653N with a prevalence of 0.5%, a mutation that has not been associated before with artemisinin resistance in Southeast Asia. In addition, other new non-synonymous mutations (M472I; Y558C; K563R; P570L; P615S) have been reported in other places but have not shown any role in conferring resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, previously reported artemisinin resistance in Southeast Asian countries and poor responses of the malaria parasites in some parts of Africa and South America remain major threats in efforts to combat malaria in the world. 20 With the possibility of malaria resistance spreading worldwide by following the previously recorded patterns of chroloquine and sulphodoxine-pyrimethamine resistance, 21 we should develop standard surveillance methods to identify the possible emergence of resistance to artemisinin combined therapies. Thus, this study was aimed at identifying the presence of K13 P. falciparum resistance markers.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium falciparum polymerase chain reaction positive (PCR +) samples were 18,292 out of 32,406 total samples collected [39][40][41][42][43][44][45], yielding PCR positivity rate of 56.4% malaria in both clinical and community…”
Section: Sample Pre-processing and Pfk13 Genotypingmentioning
confidence: 99%
“…Prompt management of malaria cases remains a vital component of malaria control and elimination strategies [ 1 ]. Over the two last decades, artemisinin (ART)-based combination therapy (ACT) has contributed significantly to the reduction of malaria-related morbidity and mortality in sub-Saharan Africa [ 2 ]. Since 2006, the Senegalese National Malaria Control Programme (NMCP) has recommended artemether–lumefantrine (AL) as the first-line treatment for uncomplicated malaria [ 3 ].…”
Section: Introductionmentioning
confidence: 99%